Language Environment: From Concept to Principles of Creation - Yu. P. Pokholkov; L. N. Goryanova (Высшее образование в России, 2022)
Language environment is now being created and cultivated in most Russian universities. However, as a concept it has been defined quite fragmentary, and in many cases is completely ignored as something obvious and self-evident. In this paper, we conduct a literature review of most typical definitions of this phenomenon and identify a set of features underlying its understanding. We then propose a more precise definition of language environment and highlight the basic principles that contribute to its effective functioning and ensure the linguistic socialization of an individual. We suggest that our “definition-assumption” and the minimum set of principles should be at the core of university measures towards creating a foreign language environment.